Reaching and teaching stressed and anxious learners in grades 4-8 : strategies for relieving distress and trauma in schools and classrooms - Oehlberg, Barbara, 1932- (NU Curriculum., 2006)
Trauma and stress can interfere with students' cognitive skills. Dicover how classroom activities can be used to restore feelings of safety, empowerment, and well-being.